STRATEGI PENGELOLAAN WISATA ALAM PERKOTAAN SEBAGAI PARIWISATA KEBERLANJUTAN DI ECOPARK TEBET - Vincentsius Valentino; Prayogo Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the existing management condition of Tebet Ecopark as a sustainable urban nature tourism destination. In addition, this study seeks to identify internal and external factors that support and hinder its management, as well as to formulate appropriate management strategies so that Tebet Ecopark can continue to function ecologically, maintain its tourism appeal, and provide a comfortable public space. This study employs a qualitative method with a descriptive approach. Data were collected through interviews, observation, documentation, and literature study. The research informants consisted of Tebet Ecopark managers, visitors, and local residents, who were selected purposively according to the data needs of the study. This method was used to obtain an in-depth understanding of Tebet Ecopark management within its real context. The results show that the management condition of Tebet Ecopark is relatively good, as it is able to support ecological, social, recreational, and economic functions. Tebet Ecopark serves as a green open space that contributes to water absorption, pollution reduction, social interaction, recreational activities, and economic activities for the surrounding community. However, several challenges remain, including the need to improve facility maintenance, strengthen environmental education, ensure a more equitable distribution of economic benefits, increase community participation, and improve the arrangement of the surrounding area. The supporting factors in the management of Tebet Ecopark include its strategic location, strong ecological function, diverse zones, and high visitor interest. Meanwhile, the inhibiting factors include visitor overcrowding, illegal parking, traffic congestion, limited facilities, and the lack of optimal community involvement. The recommended strategy is a sustainability-based collaborative management strategy involving park managers, the government, local communities, environmental groups, and MSME actors to maintain a balance among the environmental, social, and economic functions of the area.